2006
DOI: 10.1152/ajpendo.00293.2004
|View full text |Cite
|
Sign up to set email alerts
|

Two-week longitudinal survey of bone architecture alteration in the hindlimb-unloaded rat model of bone loss: sex differences

Abstract: Vico. Two-week longitudinal survey of bone architecture alteration in the hindlimb-unloaded rat model of bone loss: sex differences. Am J Physiol Endocrinol Metab 290: E440 -E447, 2006; doi:10.1152/ajpendo.00293.2004.-The goal of this study was to determine, through a longitudinal follow-up, whether sex influences bone adaptation during simulated weightlessness. Twelve-week-old male and female Wistar rats were hindlimb unweighted for 2 wk, and the time course of bone alteration was monitored in vivo by means … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
44
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(50 citation statements)
references
References 30 publications
6
44
0
Order By: Relevance
“…In a study with 1,133 patients, female sex was identified as a major risk factor for compromised fracture healing [24]. This was confirmed by other studies [25][26][27]. However, the cellular or molecular reasons for the sex-specific differences in fracture healing remain elusive.…”
Section: Discussionmentioning
confidence: 65%
“…In a study with 1,133 patients, female sex was identified as a major risk factor for compromised fracture healing [24]. This was confirmed by other studies [25][26][27]. However, the cellular or molecular reasons for the sex-specific differences in fracture healing remain elusive.…”
Section: Discussionmentioning
confidence: 65%
“…It is suggested that mechanical unloading of the bone is causative in early subchondral trabecular bone changes rather than the degenerative process itself. (35) Subchondral plate thickness was significantly reduced in both OA models, as were cartilage integrity parameters. The similarity in cartilage damage for both models was corroborated by the similarity in elevation of the cartilage collagen marker CTX-II during the course of development of the cartilage degeneration.…”
Section: Discussionmentioning
confidence: 89%
“…For simulation of SCI, animal models of limb unloading have been developed, including hind limb unloading [114][115][116] and the functionally isolated avian ulna [103]. Animal models of SCI (contusion, transection) that examine bone loss are less common because of various degrees of spontaneous recovery and the uncertainty of unloading muscle and bone in many species [117][118][119][120]).…”
Section: Bone Response To Trainingmentioning
confidence: 99%